Smaller pituitary volume in adult patients with obsessive-compulsive disorder - Atmaca, Murad; Yildirim, Hanefi; Ozler, Sinan; Koc, Mustafa; Kara, Bilge; Sec, Semih (Wiley-Blackwell Publishing, Inc, 2009)
Aims: Another structure in the obsessive compulsive disorder (OCD) circuit may be the pituitary gland because of the fact that limbic hypothalamic-pituitary-adrenal (LHPA) axis abnormality has been reported in patients with OCD. There has been only one prior study, however, concerning pituitary volumetry, in which the sample was a pediatric group. The purpose of the present study was therefore to investigate this in an adult OCD patient group using magnetic resonance imaging (MRI). Methods: Pituitary volume was measured in 23 OCD patients and the same number of healthy control subjects. Volumetric measurements were made on T1-weighted coronal MRI, with 2.40-mm-thick slices, at 1.5 T, and were done blindly. Results: A statistically significantly smaller pituitary volume was found in OCD patients compared to healthy controls (age and intracranial volume as covariates). With regard to gender and diagnosis, there was a significant difference in pituitary gland volume (F = 4.18, P < 0.05). In addition, post-hoc analysis indicated near-significant difference in men with OCD as compared with women with OCD (P = 0.07) and significant difference between control men and control women (F = 10.96, P < 0.001). Conclusions: Taking into consideration that the prior study found decreases in pituitary volume in pediatric patients with OCD as compared with healthy control subjects, future large MRI studies should investigate pituitary size longitudinally, with a careful characterization of hypothalamo-pituitary-adrenal (HPA) function in conjunction with anatomic MRI evaluation.
Keywords: magnetic resonance imaging; obsessive-compulsive disorder; pituitary; volume